Global C‐Band Envisat, RADARSAT‐2 and Sentinel‐1 SAR measurements in copolarization and cross‐polarization. Issue 11 (6th November 2015) - Mouche, A.; Chapron, B.
Abstract: Using colocated ASCAT and ECMWF winds, a careful global analysis of ENVISAT and Sentinel‐1 synthetic aperture radar (SAR) measurements helps to refine, at medium resolution (tens of kilometers) and especially for HH configuration, a C‐band geophysical model function (GMF, i.e., C‐SARMOD) to analyze wind sensitivity for different incidence and azimuth angles. Results unify major findings from previous global and case studies for polarization ratio (PR, VV/HH), polarization difference (PD, VV‐HH), and cross‐polarization (CP). At lower level than standard two‐scale predictions, PR increases with increasing incidence angle and decreases with increasing wind speed. PR further exhibits a strong azimuthal modulation, with maximum values in downwind configurations. The PD azimuth modulation is found more pronounced for VV than HH (VV being larger than HH), reaching maximum values for wind speed about 10 m/s. CP signals decrease with incidence angle but increase with wind speed, especially beyond 10 m/s, with no evidence of saturation. Remarkably, this also applies to HH crosswind measurements. This comparable high wind sensitivity for both CP and HH crosswind signals, with a clear departure from PD ones, can be related to the onset of vigorous breaking events, large enough to impact in‐plane and out‐of‐plane local tilts. Considering that VV polarization best maximizes the polarized resonant contribution, combined CP and VV wide swath SAR observations can thus have the potential to efficiently map and contrast local directional aspects. Key Points: First C‐Band GMF in VV and HH and signals in cross‐polarization from Sentinel‐1 A are presented Results unify major findings from literature for polarization combination and cross‐polarization Comparable wind sensitivity for cross‐pol and HH crosswind signals is attributed to breaking events